Relationship of perioperative anaphylaxis to neuromuscular blocking agents, obesity, and pholcodine consumption: a case-control study. (May 2021) - Sadleir, Paul H.M.; Clarke, Russell C.; Goddard, Catherine E.; Day, Conor; Weightman, William; Middleditch, Alex; Platt, Peter R.
Abstract: Background: The observation that patients presenting for bariatric surgery had a high incidence of neuromuscular blocking agent (NMBA) anaphylaxis prompted this restricted case-control study to test the hypothesis that obesity is a risk factor for NMBA anaphylaxis, independent of differences in pholcodine consumption. Methods: We compared 145 patients diagnosed with intraoperative NMBA anaphylaxis in Western Australia between 2012 and 2020 with 61 patients with cefazolin anaphylaxis with respect to BMI grade, history of pholcodine consumption, sex, age, comorbid disease, and NMBA type and dose. Confounding was assessed by stratification and binomial logistic regression. Results: Obesity (odds ratio [OR]=2.96, χ 2 =11.7, P =0.001), 'definite' pholcodine consumption (OR=14.0, χ 2 =2.6, P <0.001), and female sex (OR=2.70, χ 2 =9.61, P =0.002) were statistically significant risk factors for NMBA anaphylaxis on univariate analysis. The risk of NMBA anaphylaxis increased with BMI grade. Confounding analysis indicated that both obesity and pholcodine consumption remained important risk factors after correction for confounding, but that sex did not. The relative rate of rocuronium anaphylaxis was estimated to be 3.0 times that of vecuronium using controls as an estimate of market share, and the risk of NMBA anaphylaxis in patients presenting for bariatric surgery was 8.8 times the expected rate (74.9 vs 8.5 per 100 000 anaesthetic procedures). Conclusions: Obesity is a risk factor for NMBA anaphylaxis, the risk increasing with BMI grade. Pholcodine consumption is also a risk factor, and this is consistent with the pholcodine hypothesis. Rocuronium use is associated with an increased risk of anaphylaxis compared with vecuronium in this population.